A novel ultra-large flat plate heat pipe manufactured by thermal spray. (5th May 2020) - Feng, C.; Gibbons, M.J.; Marengo, M.; Chandra, S.
Highlights: A vapour chamber with porous copper wicks was made using thermal spraying. Dry out occurs when rate of fluid recirculation is less than rate of evaporation. A peak radial thermal conductivity of 920 W/m K was noted for a 65% filling ratio. A model was developed to calculate dry out for a given filling ratio and heat flux. Abstract: An ultra-large flat plate copper heat pipe (180 × 180 mm 2 ) was constructed using a thermal spray technique, and it was then thermally characterized. A porous copper wick was fabricated by using a flame spray torch to deposit a mixture of copper and aluminum particles onto the target substrate. A stainless-steel wire mesh acts as a mask so that the coating deposited is in the form of an array of microstructures with channels between them. After spraying, the aluminum deposit is leached away by immersing the plate in a dilute NaOH solution to produce a porous structure. A second copper plate was placed on top of the coated surface, and their edges were vacuum brazed to form a sealed enclosure. The enclosed volume was evacuated and partially filled with water to form a heat pipe. The heat pipe was centrally heated from its bottom and cooled along its top outer edge. Three liquid filling ratios and six heat fluxes from 2.5 W/cm 2 to 15 W/cm 2 were investigated. A decreasing lateral thermal resistance for an increasing applied heat flux was noted for all filling ratios until central dry-out. Central dry-out corresponds to the point where the evaporation rate outpaces the wicking of the working fluid at the centre of the heat pipe. Dry-out of the central wick results in a large thermal resistance compared to the pre-dry-out condition. Delayed dry-out onset was noted for increasing working fluid filling ratios. In the pre-dry-out condition, a peak average radial thermal conductivity of 920 W/m K was noted for a 65% filling ratio, and 7.5 W/cm 2 applied heat flux. A model was generated to calculate dry-out of the thermally sprayed porous wick for a given filling ratio and applied heat flux. The present research represents two highly novel advances in heat pipe technology. The first is the development of a new innovative manufacturing technique for the generation of a porous wick structure within a heat pipe. This new manufacturing technique enables the production of large metal vapour chambers with complex 3D geometries. When applied in conjunction with copper compatible working fluids, this techniques facilitates the realization of skin thermal conductors. Second, the fabrication of an ultra-large flat plate heat pipe that is significantly larger than that previously reported in the literature is demonstrated.